Marketing estratégico para incrementar ventas de la línea Em Décor en la Empresa Expomedios, zona norte de la ciudad de Guayaquil - Bucheli Caballero, Lissette Elizabeth (2019)
This research project aimed to develop Marketing Strategies that allow the Expomedios Enterprise to increase the sales in the EM Décor Line at Garzota Showroom. This line offers products such as Vinyl, upholstery paper, PVC floors for ambiance decoration, this line has passed after ten years in the market in a stage of Maturity, with a decrease of 12% in sales, the same which haven’t increased due to the marketing strategies lack which would allow to defend the brand in the marketplace. Issues like this, happens because there is no differentiation that determines a competitive advantage that makes it sole in front of the direct and indirect competitors. Indirect competitors are positioned with substitute low cost products……….